2002
DOI: 10.1021/np0202632
|View full text |Cite
|
Sign up to set email alerts
|

Three New Guaianolides from Siyekucai (Ixeris chinenseis)

Abstract: Three new guaianolides, 10alpha-hydroxy-3-oxoguaia-4(15),11(13)-dieno-12,6alpha-lactone (1), 10alpha-hydroxy-3-oxo-4betaH-guaia-11(13)-eno-12,6alpha-lactone (2), and 10alpha-hydroxy-3-oxoguaia-4,11(13)-dieno-12,6alpha-lactone (3), named chinensiolides A, B, and C were isolated from the whole plant of Siyekucai (Ixeris chinensis). The structures were determined by HREIMS, UV, IR, and one- and two-dimensional NMR techniques ((1)H and (13)C NMR, COSY, HMQC, HMBC, and NOE difference and NOESY experiments). Compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…It was at this point that we realized, with great distress to both of us, that the spectral data for our synthetic sample of putative chinensiolide B did not match that reported in the original isolation paper. 5 The 1 H NMR data showed that some of the peaks were close in chemical shift (within 0.1 ppm) to the reported values; however, others were quite different (up to 0.5 ppm difference). The 13 C NMR spectrum also had some peaks that were identical in chemical shift and others that were significantly different (>1 ppm difference).…”
Section: A Comparison Of Our Spectral Data With the Literaturesupporting
confidence: 59%
See 2 more Smart Citations
“…It was at this point that we realized, with great distress to both of us, that the spectral data for our synthetic sample of putative chinensiolide B did not match that reported in the original isolation paper. 5 The 1 H NMR data showed that some of the peaks were close in chemical shift (within 0.1 ppm) to the reported values; however, others were quite different (up to 0.5 ppm difference). The 13 C NMR spectrum also had some peaks that were identical in chemical shift and others that were significantly different (>1 ppm difference).…”
Section: A Comparison Of Our Spectral Data With the Literaturesupporting
confidence: 59%
“…4 Chinensiolide B (1, Figure 1) constitutes another fascinating example of a natural product containing the a-methylene g-lactone unit as part of a tricyclic 5-7-5-ring structure. There are five members of this family of sesquiterpenes that have been isolated and characterized to date, 5,6 and the structure of chinensiolide B is shown in Figure 1. The chinensiolide natural products are isolated from rabbit milkweed (Ixeris chinensis Nakai), a perennial plant that grows in various parts of China.…”
Section: Chinensiolide and Other A-methylene G-lactones In Naturementioning
confidence: 99%
See 1 more Smart Citation
“…Guaianolide derivatives possessing a-methyleneg-lactone moieties, such as dehydrocostus lactone, exert inhibitory effects at IC 50 values lower than 10 mM, whereas other a-methyl-glactone derivatives show much weaker inhibitory effects. [76][77][78] These findings clearly show that an a-methylene-g-lactone moiety is crucial to inhibit the induction of ICAM-1 expression. This notion is consistent with the structure-activity relationship study of the effect of sesquiterpene lactones on NF-kB-binding activity in TNF-a-stimulated cells, which shows that various guaianolides and eudesmanes containing a-methylene-g-lactones manifest inhibitory effects.…”
Section: Thiol-reactive Ikk Inhibitorsmentioning
confidence: 70%
“…6) Their biological activities have been attributed to their reactivity with the cysteine residues of functional proteins forming covalent bonds. 7) Six guaianolides 8,9) in addition to forty triterpenoids 10,11) were previously isolated from this species. The present study is concerned with the isolation and structural elucidation of two new guaianolides, ixerochinolide (1) and a related glucoside, ixerochinoside (2).…”
mentioning
confidence: 99%